Climate trends account for stalled wheat yields in Australia since 1990. (24th January 2017) - Hochman, Zvi; Gobbett, David L.; Horan, Heidi
Abstract: Global food security requires that grain yields continue to increase to 2050, yet yields have stalled in many developed countries. This disturbing trend has so far been only partially explained. Here, we show that wheat yields in Australia have stalled since 1990 and investigate the extent to which climate trends account for this observation. Based on simulation of 50 sites with quality weather data, that are representative of the agro‐ecological zones and of soil types in the grain zone, we show that water‐limited yield potential declined by 27% over a 26 year period from 1990 to 2015. We attribute this decline to reduced rainfall and to rising temperatures while the positive effect of elevated atmospheric CO2 concentrations prevented a further 4% loss relative to 1990 yields. Closer investigation of three sites revealed the nature of the simulated response of water‐limited yield to water availability, water stress and maximum temperatures. At all three sites, maximum temperature hastened time from sowing to flowering and to maturity and reduced grain number per m 2 and average weight per grain. This 27% climate‐driven decline in water‐limited yield is not fully expressed in actual national yields. This is due to an unprecedented rate of technology‐driven gains closing the gap between actual and water‐limited potential yields by 25 kg ha −1  yr −1 enabling relative yields to increase from 39% in 1990 to 55% in 2015. It remains to be seen whether technology can continue to maintain current yields, let alone increase them to those required by 2050. Abstract : We investigated why Australia's wheat yields have stalled since 1990 by simulating yields at 50 representative sites in the grain zone. Yield potential declined by 27% over 26 years. We showed that this is due to declining rainfall and to rising temperatures while the positive effect of elevated atmospheric CO2 concentrations prevented a further 4% loss. This climate‐driven decline in yield potential was balanced by an unprecedented rate of adoption of technology‐driven gains closing the gap between actual and potential yields.